Interactive Learning Tasks as an Effective Means of Studying Jaloliddin Rumi's Educational and Moral Views (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article analyzes the importance of interactive learning tasks in deeply teaching Jaloliddin Rumi’s educational and moral views to students. It also explores ways of adapting Rumi’s ideas to the educational process, activating students’ thinking, and strengthening moral education